Metode Bernyanyi (At-Thariqah al-Ghina’iyyah) dalam Menanamkan Konsep Angka Bahasa Arab secara Holistik pada Siswa SD - Praja Pramudyaningsih; Faisal Hendra (Educational Journal, 2026)
This study aims to analyze the effectiveness of the singing method (At-Thariqah al-Ghina’iyyah) in teaching the concept of Arabic numerals holistically to elementary school students. This research employed a qualitative approach using a library research design. Data were collected through documentation studies of scholarly journals, books, and previous research related to the singing method, Arabic language learning, and holistic education. The data were analyzed using content analysis to identify, examine, and synthesize findings from relevant literature. The results indicate that the singing method is effective in improving students' understanding, memory retention, learning motivation, and interest in Arabic numerals. The integration of music, rhythm, and movement in the learning process enhances students' cognitive, affective, and psychomotor development. Furthermore, this method creates an active, enjoyable, and meaningful learning environment, thereby supporting more effective Arabic language learning at the elementary school level.